ON THE RABIN’S SPEED-UP OF PROOFS FOR SOME SYSTEMS OF FIRST ORDER LOGIC - Chubaryan, A. A.; Bolibekyan, H. R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2010)
In the paper a notion of ordinary theory is considered. It is proved that some systems of first order predicate calculus are ordinary. This property is used for a proof complexity comparison in the considered systems.